(untitled) - Strebe, Matthew (San Francisco, 1997)
The coverage spans every aspect of the NT Server course, including installing, configuring, and administering NT Server networks. A test-simulation program, provided on the companion CD, lets you study and review sample test questions, and identify areas requiring further work
Keywords: Electronic data processing personnel,Microsoft software,Nhân viên xử lý dữ liệu điện tử,Microsoft Windows NT Server,Phần mềm Microsoft,Máy chủ Microsoft Windows NT; Certification,Examinations,Chứng nhận,Bài kiểm tra